Raman identification of olivine grains in fine grained mineral assemblages fired into aerogel. (2017) - Wickham-Eade, Jamie E.; Burchell, Mark J.; Price, Mark C.; Hicks, Leon J.; MacArthur, Jane L.; Bridges, John C.
Abstract: NASA's Stardust mission returned from the comet 81P/Wild2 in 2006 and has yielded a plethora of research looking into the composition and attributes of the comet. The mission itself collected thousands of cometary dust particles as it flew through the coma of the comet at a relative speed of 6.1 km s -1 . This work focuses on one of the most abundant minerals in the solar system – olivine. Previous work has shown capture affects on this mineral in similar impacts to that experienced during the Stardust mission. However, the past work looked into effects on isolated mineral grains which would be a rare occurrence in the Solar System. A more accurate representation of this would be to investigate the capture effects on olivine as a constituent of an assemblage of minerals. Accordingly, here we used samples from the NWA 10256 CR2 carbonaceous chondrite meteorite. This natural sample contains fine grains of olivine, and brings additional issues when analysing the olivine due to limited homogeneity. Shifts in the Raman spectra for olivine, enstatite and hematite were observed after capture due to shock effects. However, this work suggests that olivine may well experience a different shock effect during capture when part of a mineral assemblage as distinct from that experienced by single grains.